Explanation:
For Particle A:
The net gravitational force is the sum of the two forces due to particle B and due to particle C. Both of these particles have positive direction.
[tex]F_{A} = F_{BA} + F_{CA} = G\frac{m_{B} m_{A} }{r_{AB} ^{2} } + G\frac{m_{C} m_{A} }{r_{AC} ^{2} }[/tex]
[tex]= 6.67*10^{-11}\frac{517*363}{0.5^{2} } +6.67*10^{-11} \frac{154*363}{0.75^{2} }[/tex]
= [tex]5.7*10^{-5}[/tex] N
For Particle B:
The net gravitational force is the sum of the two forces: due to particle A and due to particle C. The force due to particle A is negative as its direction is to left. The force due to particle C is positive.
[tex]F_{B} =- F_{BA} + F_{CB} = G\frac{m_{B} m_{A} }{r_{AB} ^{2} } + G\frac{m_{C} m_{B} }{r_{BC} ^{2} }[/tex]
[tex]= -6.67*10^{-11}\frac{517*363}{0.5^{2} } +6.67*10^{-11} \frac{154*517}{0.25^{2} }[/tex]
= [tex]3.48*10^{-5}[/tex]N
For particle C:
The net gravitational force is the sum of two forces: due to particle A and due to particle B. Both forces are negative then,
[tex]F_{C} =- F_{BC} + F_{CA} = -G\frac{m_{B} m_{C} }{r_{CB} ^{2} } + G\frac{m_{C} m_{A} }{r_{AC} ^{2} }[/tex]
[tex]= -6.67*10^{-11}\frac{517*154}{0.25^{2} } +6.67*10^{-11} \frac{154*363}{0.75^{2} }[/tex]
= [tex]-7.8*10^{-5} N[/tex]